Study on the development of liquid extract of cardiotonic action - O. S. Kukhtenko; N. Y. Bevz; Ie. V. Gladukh; H. P. Kukhtenko (Фармацевтичний журнал, 2019)
At the Department of Industrial Pharmacy of the National University of Pharmacy, a complex cardiotonic action extract containing extracts of Crataegus охуaсanta fruits, Leonurus cardiaca herb, Melissa officinalis herb and Humulus lupulus seedballs in equals proportions is being developed.